Transformation of Learning Media In Enhancing Arabic Language Competence: A Case Study at The Arabic Language Education Study Program UIN STS Jambi - Uluum, Dina Chabib; Syamsiyah , Dailatus; Yusraini, Yusraini (FKIP - Universitas Riau, 2025)
This research is motivated by the demands of the digitalization era requiring the transformation of Arabic language learning media to enhance student competence in the Arabic Language Education Study Program at UIN Sultan Thaha Saifuddin Jambi. The research objective is to explore the forms of learning media transformation, driving factors, and its impact on students' Arabic language competence. The research method employs a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The research findings show that learning media transformation includes the transition from conventional to digital media, integration of interactive multimedia technology, and development of adaptive learning platforms. The driving factors of transformation include the demands of the digitalization era, institutional policies, and the needs of digital native generations. In conclusion, the transformation of learning media makes a significant contribution to student competence, with recommendations for implementing sustainable strategies that consider pedagogical, technological, and contextual aspects.